Registry users and producers of spatial data in the Federation of Bosnia and Herzegovina - Slobodanka Ključanin (Geodetski Glasnik, 2016)
In the Federation of Bosnia and Herzegovina, which has a complex political system (10 cantons and 79 municipalities), the collection and use of spatial data is a demanding job. A demanding job because the responsibilities of institutions are not clear-cut, and thus leads to duplication of data and user confusion regarding the accuracy of the data it uses. Progress, in terms of improving the situation, could be achieved by using the rules of the INSPIRE Directive. However, the INSPIRE directive is not binding for the Federation of Bosnia and Herzegovina. In practice, however, went into the creation of prerequisites for the implementation of Spatial data infrastructures of the Federation of BiH (IPPFBIH) (Regulation on the establishment and implementation of IPPFBIH Council IPPFBIH, Strategy IPPFBIH). The strategy describes the way towards the establishment and implementation of IPPFBIH. One of the first projects to be done is the establishment of the Register of Entities and the Register of spatial data resources. This article talks about how they were formed registries in Croatia, and the Register of users and producers of spatial data in the Federation. Their establishment and comparison, did require a lot of time and effort.